(untitled) (Boletin Médico de Postgrado, 2022)
With the aim of describing the clinical and paraclinical characteristics of brain salt wasting syndrome (SCPS) in patients with cerebral vascular disease (CVD) who were admitted to the Internal Medicine Department of the Dr. Antonio María Pineda Central University Hospital during the period April-July 2020, a cross-sectional descriptive study was conducted with a sample of 29 patients who were characterized by an average age of 61.55 ± 12.92 years with a predominance of male sex (55.17%). 65.52% of the patients presented hemorrhagic and 34.48% ischemic CVD, with an average evolution time of 2.45 ± 1.81 days. Improvement was observed in the mean values of serum sodium, plasma osmolarity, urinary osmolarity and urinary sodium, between admission, day 3, 7 and 10 (p < 0.05) in contrast to glycemia whose variations were not significant (p = 0.17). 57.89% of the patients with hemorrhagic CVD presented moderate hyponatremia and in 60% of the patients with ischemic CVD the hyponatremia was severe. The clinical evolution was favorable in 73.68% of patients with hemorrhagic CVD and 50% with ischemic CVD. Sodium alterations can negatively affect the neurological evolution of patients with CVE, increasing hospital stay and mortality rate. These results provide real and updated information on the frequency of SCPS in patients with CVE in our hospital.